Negócios jurídicos na arbitragem - Barabino, André (2017)
The arbitration is related to Civil Law, considering that its genesis, the arbitration clause, whereby the parties choose the arbitral jurisdiction for the resolution of conflicts, has an intimate relationship with private law, reason why it shall observe certain requisites relative to the legal transactions. In the course of an arbitration proceeding, there are various obligation relationships established between the parties, arbitration center and the arbitrators, as well as several legal transactions are formed, with its unique requirements. Examples of the contractual relationship formed on arbitration are the arbitration clause, the term of reference, the term which the parties choose and invest jurisdictional powers to the arbitrator sand the contracting of an institutional center to administrate the arbitration proceeding. Each of these contractual relationships have their own characteristics and shall observe the requirements established in articles 104 and 425 of the Brazilian Civil Code. Therefore, the purpose of this dissertation is to analyze the contractual relationships, as well as the requirements each of these legal transactions of the arbitration shall have to be existent, valid and effective